Leadership and Pedagogical Values of Ganjar Pranowo's Education: Case Study of Mothers in the DMC Gymnastics Community - Fuad Rinaldi; Iik Nurul Fatimah (Edumaspul: Jurnal Pendidikan, 2023)
This research is motivated by the importance of leadership and pedagogical values. This research aims to analyze and explain the Leadership and Educational Pedagogical Values of Ganjar Pranowo (Case Study of Mothers in the DMC Gymnastics Community). This research uses a qualitative research method with a case study approach and is descriptive. Data collection techniques are observation, interviews and documentation. The informants/sources of information in this research were administrators and members of the DMC gymnastics community. The data analysis techniques used are data reduction, data presentation and verification. The results of this research explain: 1) Leadership is an activity to influence people so that they are directed towards achieving organizational goals. Leadership includes the process of influencing in determining organizational goals, motivating the behavior of followers to achieve goals, influencing to improve the group and its culture, 2) Pedagogical values generally refer to values related to the education and learning process in life which have an important role in directing holistic individual development, and 3) Ganjar Pranowo's leadership and pedagogical values that can be embraced and understood include being firm, intelligent and confident; Be a role model, be disciplined in carrying out your duties, be able to motivate members, and have good communication skills.